KONDISI PENDIDIKAN DASAR DI SAMBAS SEBAGAI WILAYAH PERBATASAN TAHUN 2013 - eliyah (Cross-border, 2020)
This study aims to describe the condition of basic education, both Private Madrasah Ibtidaiyah (MIS) and Public Elementary Schools (SDN) in Sambas Regency. The research method used is qualitative-descriptive. The data collection techniques used are: interviews, observation and document tation with data validity techniques are triangulation of sources and methods. The results of the study were as follows: Generally, the condition of education in Madrasah Ibtidaiyyah Kabupaten Sambas is far from perfect. Physical conditions such as buildings, facilities and infrastructure are inadequate. Lack of classes, meaning that basic education should be 6 classrooms, but madrasas only have 3 classrooms, or 5 classrooms. So that students have to even share classes without boundaries, even the blackboard has to share. But there are also madrasas that divide the students into attending lessons. Like second grade comes in after first grade comes home. The same conditions also apply to public elementary schools. Lack of classrooms is a natural sight in the world of education in Sambas Regency. Likewise with the qualifications and competencies of teachers who teach. Teachers who teach are individuals who really sincerely do good. So that when their competence must be measured in a professional manner, they are lagging far behind. But when viewed from their progress, seriousness and struggle, they are truly original "Heroes without Merits". Serve your best with minimal appreciation. So, it means that if the teacher competency condition in Sambas Regency is far behind other regions in Indonesia, it is normal. However, if the teachers are in the district Some of the Sambas are competing the same and some even stand out from other teachers in the Indonesian region, which means "Extraordinary". Because limitations do not become an obstacle to continue achieving.